STRATEGI UMKM UNTUK MENGHADAPI PERUBAHAN EKONOMI PADA MASA PANDEMI DEMI KEBERLANGSUNGAN USAHA - Bowo, Antaiwan Bowo Pranogyo (AKSIOMA : Jurnal Manajemen, 2023)
Micro, small and medium corporations are humans monetary sports that make a contribution to accelerating the recuperation from the monetary crisis in Indonesia. Micro, Small, and Medium corporations (MSMEs) are enterprise sectors that have a vital function within the financial system and may live to tell the tale all through the financial crisis in Indonesia. for the duration of the COVID-19 pandemic, many perpetrators experienced difficulties. The issue of acquiring uncooked materials, hampering production and distribution, the lack of facts era expertise and the obstruction of business networks makes MSME actors should innovate. Because of this, it’s miles necessary to increase its competitiveness. robust synergy from MSME actors in the agency will boom competitiveness, a good way to accelerate their enterprise growth, This research targets to find out, perceive, review, examine and interpret all studies that have been achieved previously, This research ambitions to discover the business strategies applied with the aid of Micro, Small, and Medium establishments (MSMEs) in dealing with the Covid-19 pandemic., The approach used is the technique qualitative studies with a descriptive technique, The consequences of the identity are anticipated to add to the literature on Micro, Small, and Medium businesses (MSMEs) that have a role in the Indonesian economy in addition to the authorities’ efforts to resolve a problem as a way to have an effect on the financial system including poverty and unemployment.